AVIAN DIVERSITY IN THE NAPO-PUTUMAYO-AMAZONAS INTERFLUVIUM, NORTHERN PERUVIAN AMAZON - ANGULO-PEREZ, Natalia C. (2020)
The study of avian habitats is essential to understanding species abundance, diversity and distribution. For this reason, a survey of transects and mist net studies were reviewed to ascertain the ornithological richness in the Napo- Putumayo-Amazonas interfluvium, including its composition by habitat types, threatened species and main threats. Analyses conducted included a comparison of observed and expected diversity, as well as the similarities between flooded habitats (swampy varillal and mixed palm swamp) and terra firme (low hill, high terrace and middle terrace). With over 558 species registered, more than 50 % of the estimated species for Loreto were represented, with the low hill forest containing the highest species richness. The composition of species varies by type of floodplain and terra firme habitat, but both habitats / ecosystems share species, with the middle terrace being home to species found in the flooded forest and terra firme. The families Thamnophilidae, Tyrannidae and Furnariidae are the best represented in all habitats. The avifauna is very diverse and is home to unique, threatened and potential bird species. Unfortunately, the area also faces threats that endanger avian survival through the loss of habitat due to deforestation, migratory agriculture, the cultivation of Erythroxylum coca and/or the timber industry, species trafficking and overhunting. As such, it is important to implement management plans for avian species, focusing on priority habitats or tourism schemes that guarantee avian conservation.